Literature Review: Pengaruh Aloe Vera Terhadap Penyembuhan Luka Diabetik Pada Pasien Diabetes Melitus - Naibaho, Elria Debora; Mahasari, Denida; Hidayat, Sutiawati; Rahayu, Suci; Mulyani, Utami; Susanto, Adi Dwi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Diabetes mellitus is a chronic disease that often leads to complications in the form of diabetic wounds, which are difficult to heal. One of the widely studied nonpharmacological approaches is the use of Aloe vera, which is known to have anti-inflammatory, antibacterial, and tissue-regenerating properties. This study aims to review the effectiveness of Aloe vera in diabetic wound healing based on recent literature. The method used was a literature review by searching articles in PubMed, ScienceDirect, and Google Scholar databases. Inclusion criteria were studies published between 2019 and 2025 with clinical trial, quasi-experimental, or case study designs involving patients with diabetic wounds and using Aloe vera as the main intervention. Data were analyzed using a narrative synthesis by comparing findings across studies. A review of eight articles showed that Aloe vera promoted granulation tissue formation, accelerated epithelialization, and reduced wound exudate. Several studies demonstrated significant improvements compared to control groups, while others emphasized that effectiveness depended on treatment duration, wound condition, and additional techniques such as debridement. Innovations identified included combining Aloe vera with other natural agents and the development of dressings based on Aloe vera extract to enhance healing outcomes. In conclusion, Aloe vera has the potential to serve as a safe, affordable, and supportive complementary therapy for diabetic wound management, particularly when applied in synergy with standard care.